Endangered animals - Brundle, Harriet; Kissock, Heather (Awesome infographics., 2021)
Presents a series of colorfully illustrated infographics with statistics and trivia on some of the world's animals that are in danger of becoming extinct, and what is putting them into the endangered category--things like climate change and pollution. Includes a glossary.